(untitled) (MCIT: Proceedings of International scientific and practical conference, 2021)
Polynomial matrices and of size over a field are semi-scalar equivalent if there exist a nonsingular matrix over and an invertible matrix over such that . The aim of the present report is to present a triangular form of some nonsingular polynomial matrices with respect to semi-scalar equivalence.